PENGARUH FOCUS GROUP DISCUSSION TENTANG PELAKSANAAN UJI KOMPETENSI TERHADAP TINGKAT KECEMASAN MAHASISWA - Benny Andreson Situmorang; Kristina L Silalahi (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2019)
The Indonesian National Competency Test (INCT) is carried out with the aim of equalizing the quality standards of graduates at each educational institution. For INCT students is a challenge that must be faced because to apply for a job a health worker must have a registration certificate (RC). The registration certificate is obtained if a student is declared a graduate (competent) in the implementation of Competency Test. The purpose of this study is to obtain information on the problems being faced by professional nurses who will face the Indonesian National Competency Test through the implementation of Focus Group Discussion (FGD). This type of research is qualitative research with a quasi-experimental research design with one group pretest-posttest design. Stages of Research Methods will be carried out using the design of the quasi-experiment(quasi-experimental) with the target of all nurses in the final semester of totaling 51 people. Data collection method with guided interview guidance. The data analysis method uses dependent t-test. Where in the paired groups, the same subject was examined before and after the intervention (design before and after) and at the same time. Based on the results of the t-test calculation, the value of Z -4,472 with (p = 0,000) <0.05 so that the decision of the hypothesis Ha is accepted then H0 is rejected. It was concluded that there was an influence between FGD (Focus Group Discussion) on the Implementation of Competency Tests on the anxiety level of Nurse Profession students at FKK UNPRI Medan in 2019. It is expected that students who will face competency tests to prepare themselves more by following guidance both on campus and outside campus so have good preparation in facing the Competency Test Keywords: Focus Group Discussion, implementation, competence, test, anxiety level